Unveiling the Robust Struct-Electromagnetic Characteristics of CdAB2 Chalcopyrite (A = Cr, Mn, Fe; B = P, As): A Comprehensive Ab-Initio Study - D. Vijayalakshmi; Tholkappiyan Ramachandran; G. Jaiganesh; G. Kalpana; Fathalla Hamed (Advances in Condensed Matter Physics)
We present a comprehensive investigation of the electromagnetic properties of CdAB2 compounds, where A represents Cr, Mn, or Fe, and B denotes P or As. To investigate the spin-polarized behavior of these compounds the A atoms were substituted at the Group IV (Ge) position in CdGeB2 in the chalcopyrite crystal structure. Our results reveal that all the CdAB2 compounds exhibit compelling spin-splitting of energy states near the Fermi level (EF). Notably, CdAB2 materials with A = Cr and Mn exhibit intriguing half-metallic ferromagnetic (HMF) characteristics, with the calculated total magnetic moments of 2.00 and 3.00 µB/f.u., respectively. The HMF properties originated in CdAB2 (A = Cr and Mn; B = P, As) these compounds owing to the hybridization of partially filled -3d(t2g) states of A atoms with the p-states of B (P, As) atoms, with minor contributions from Cd’s-like states. In contrast, CdFeB2 displays distinct behavior, demonstrating spin-splitting of energy levels around the EF indicative of a stable ferromagnetic (FM) state and the absence of HMF at their equilibrium volume. The calculated total magnetic moments for CdFeP2 and CdFeAs2 are about 1.83 (1.64 µB/f.u.) and 1.94 µB/f.u. (1.84 µB/f.u.) under generalized gradient approximation (GGA) (local spin density approximation (LSDA)) approximations, respectively. Perhaps these CdAB2 compounds (A = Cr and Mn; B = P, As) with HMF characteristic within both LSDA and GGA formalisms makes them highly promising candidates for spin injectors in the spintronic device applications. Furthermore, their semiconducting nature renders CdCrB2 and CdMnB2 materials compatible with silicon and other semiconducting lattices, enhancing their potential practical applications in the spintronic technologies. In conclusion, this study presents a thorough exploration of the robust electronic and magnetic properties of CdAB2 chalcopyrites, offering exciting prospects for their utilization in the future spintronic applications.